2016
DOI: 10.1161/jaha.116.003354
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Late Vascular Inflammation on Long‐Term Outcomes Among Patients Undergoing Implantation of Drug Eluting Stents: Role of C‐Reactive Protein

Abstract: BackgroundElevation of C‐reactive protein (CRP) as a marker of vascular inflammation at a late phase of drug‐eluting stent (DES) implantation may predict subsequent major adverse cardiac events (MACE).Methods and ResultsIn 1234 consecutive patients undergoing DES implantation, CRP was measured both before (baseline) and 8 to 12 months after (late phase) stenting, and the relationship between elevation of CRP (>2.0 mg/L) and subsequent MACE (all cause death, nonfatal myocardial infarction, target lesion revascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Consistent with these results, Shiba et al in their retrospective study of more than 1200 consecutive patients measured CRP at baseline and 8-12 months post-PCI. They confirmed that late-phase CRP is an independent predictor of MACE including TLR in patients treated with DES (76).…”
Section: Drug Eluting Stentsmentioning
confidence: 66%
“…Consistent with these results, Shiba et al in their retrospective study of more than 1200 consecutive patients measured CRP at baseline and 8-12 months post-PCI. They confirmed that late-phase CRP is an independent predictor of MACE including TLR in patients treated with DES (76).…”
Section: Drug Eluting Stentsmentioning
confidence: 66%
“…A study on 1, 234 patients undergoing DES implantation showed that high levels of CRP (>2 mg/dl) were detected in 38% of patients at baseline and in 23.6% during late phase, both stages associated with a higher risk for major cardiac adverse events (MACE). Moreover, high CRP level in the late phase was a better predictor of MACE compared to the CRP level at baseline ( 14 ). Our findings are relatively similar with the current literature data.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting the pleiotropic effects of statins that are involved in inflammatory suppression [35]. This may partly explain some findings that hs-CRP level at 8-12 months after PCI showed more profound value in predicting long-term outcomes [36,37]. This may be a possible reason that hs-CRP was excluded from the adjusted regression model for adverse events.…”
Section: Discussionmentioning
confidence: 99%